Pengaruh Self Efficacy dan Locus Of Control terhadap Kinerja Karyawan Perbankan - Heriswanto, Heriswanto; Asma Nur Islami; Irham Natsir; Fitria Fitria; Irdawati Irdawati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
. This study aims to determine and analyze the Influence of Self Efficacy and Locus of Control on Employee Performance of PD. BPR Bahteramas Konawe partially and simultaneously. This study uses a quantitative descriptive associative research method, with independent variables of Self Efficacy and Locus of Control. While the dependent variable is Employee Performance. The number of samples obtained was 31 respondents of PD. BPR Bahteramas Konawe employees. The data used is primary data with a research instrument in the form of a questionnaire. The data analysis technique used is multiple linear regression analysis using SPSS Version 23. The results of the study stated that simultaneously the variables Self Efficacy and Locus of Control have a significant effect on employee performance of PD. BPR Bahteramas Konawe. While partially the variable Self Efficacy has no significant effect on Employee Performance and the variable Locus of Control has a significant effect on employee performance of PD. BPR Bahteramas Konawe. The implications of the research results are expected to contribute to improving company and organizational performance.